2021
DOI: 10.3390/ijerph18063056
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hybrid Deep Neural Networks (HDNNs), Computed Tomography, and Chest X-rays for the Detection of COVID-19

Abstract: COVID-19 syndrome has extensively escalated worldwide with the induction of the year 2020 and has resulted in the illness of millions of people. COVID-19 patients bear an elevated risk once the symptoms deteriorate. Hence, early recognition of diseased patients can facilitate early intervention and avoid disease succession. This article intends to develop a hybrid deep neural networks (HDNNs), using computed tomography (CT) and X-ray imaging, to predict the risk of the onset of disease in patients suffering fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 40 publications
0
67
0
Order By: Relevance
“…The detection pipeline is a general framework and there are no strict restrictions. Hence, one could apply the same process to, for example, CT scan images [ 64 ], and even other areas such as those discussed in [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detection pipeline is a general framework and there are no strict restrictions. Hence, one could apply the same process to, for example, CT scan images [ 64 ], and even other areas such as those discussed in [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…where β 2 is a coefficient parameter to compute the EWA between v t−1 and g t . From Figure 8 and Equation ( 21), we can find that the long-term velocity control function is a momentum of β 2 1,t−1 (m t−1 − g t ) 2 . Accordingly, HyAdamC accumulates β 2 1,t−1 (m t−1 − g t ) 2 using the EWA to utilize a degree of these long-term average variations in the next steps.…”
Section: Long-term Velocity Control Functionmentioning
confidence: 95%
“…In particular, modern neural network models are consisted of deeper layers and more weights than traditional ones to maximize their performance. Accordingly, the latest deep learning models have shown notable abilities in many real-world applications, for example, computer visions (CV) [1,2], data analysis [3,4], personalized services [5,6], internet of things (IoT) [7,8], and natural language processing (NLP) [9,10], et al Among them, particularly, the CV task involving image classification and image semantic segmentation is one of the applications in which the deep learning models have been most actively used. Accordingly, many studies to improve the image processing ability of CNNs are being actively conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The pictorial data from chest X-ray images could be an alternative approach to the PCR screening technique. Many studies such as [ 20 , 21 ] depict the chest imaging of the body could help diagnose COVID-19. Radiologists have also found that patients with symptoms of COVID-19 have CT characteristic imaging features on their lungs, such as peripheral ground-glass opacities and consolidations, which can separate the patient infected with Coronavirus from those diseased with no Coronavirus [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%